Effect of lncRNA H19 on Rats with Chronic Heart Failure Based on TGF-β1/Smad3 Signaling Pathway - WANG Lingyan; CAO Guojun; MEI Yang; ZHANG Bin; ZHOU Shijing (康复学报)
ObjectiveTo explore the effect of long non-coding RNA H19 (lncRNA H19) and microRNA (miRNA)-200a on cardiac function and myocardial fibrosis in rats with chronic heart failure based on transforming growth factor-β1 (TGF-β1)/Smad homolog 3 (Smad3) signaling pathway.MethodsA total of 60 clean grade adult healthy male SD rats were randomly divided into sham surgery group and model group. The model group were selected to construct rats model of chronic heart failure by ligation. After successful modeling, the model rats were randomly divided into heart failure group, lncRNA H19 negative control group (negative control group), lncRNA H19 overexpression group (overexpression group) and lncRNA H19 overexpression+miRNA-200a overexpression group (combined overexpression group), with 12 rats in each group. At the 1st, 4th, 7th, 10th, 13th and 16th day, the negative control group, the overexpression group and the combined overexpression group were injected intravenously with lncRNA H19 negative control plasmid at 5 mL/(kg·d), lncRNA H19 plasmid at 5 mL/(kg·d), lncRNA H19 plasmid at 5 mL/(kg·d) and miRNA-200a plasmid at 2 mL/(kg·d) in the tails respectively; the heart failure group and the sham surgery group were only injected with equal dose of normal saline, once a day. Two days after the last injection, color Doppler ultrasound was used to detect cardiac function indexes [left ventricular ejection fraction (LVEF), left ventricular fractional shortening (LVFS), left ventricular end-systolic dimension (LVESD), left ventricular end-diastolic dimension (LVEDD)]; Masson staining was used to detect myocardial fibrosis and collagen volume fraction (CVF); real-time fluorescence quantitative PCR was used to detect the transcription level of lncRNA H19 and miRNA-200a in myocardial tissue of rats; Western blot method was used to detect the protein expression level of TGF-β1 and Smad3 in myocardial tissue of rats.ResultsCompared with sham surgery group, the protein expression level of LVEDD, LVESD, TGF-β1, Smad3 and transcription level of miRNA-200a in the other four groups significantly increased, while the protein expression level of LVFS, LVEF and transcription level of lncRNA H19 significantly decreased (P<0.05); compared with the heart failure group and the negative control group, the protein expression level of LVEDD, LVESD, TGF-β1, Smad3 and transcription level of miRNA-200a in the overexpression group and the combined overexpression group significantly decreased, while the protein expression level of LVFS, LVEF and transcription level of lncRNA H19 significantly increased (P<0.05); compared with the overexpression group, the protein expression level of LVEDD, LVESD, TGF-β1, Smad3 and transcription level of miRNA-200a in the combined overexpression group significantly increased, while LVFS and LVEF significantly decreased (P<0.05), and the transcription level of lncRNA H19 was not statistically different (P>0.05). In the sham surgery group, only a small amount of collagen was distributed in the myocardium, and the tissue cells were closely arranged without obvious gaps; compared with sham surgery group, there was a large amount of collagen hyperplasia in the myocardial tissue of rats in the heart failure group, the cell arrangement was not uniform, and CVF increased significantly (P<0.05); compared with the heart failure group and the negative control group, the myocardial collagen proliferation in the overexpression group relieved significantly, the cells were neatly distributed, and the CVF decreased significantly (P<0.05); compared with the overexpression group, there was still a large amount of collagen distribution in the myocardial tissue of rats in the combined overexpression group, the intercellular space was enlarged, and the CVF increased significantly (P<0.05).ConclusionOverexpression of lncRNA H19 can reduce the extent of myocardial fibrosis and cardiac injury and improve heart function, which may be related to the regulation of TGF-β1/Smad3 signaling pathway and the inhibition of miRNA-200a expression.